Molecular Dynamics Simulation of the Pyrolysis and Oxidation of NEPE Propellant. Issue 12 (4th November 2022) - Wen, Zhengcheng; Zhao, Xiang; Li, Heping; Huang, Xuefeng; Wang, Fang; Li, Wei; Tang, Gen; Feng, Muye
Abstract: NEPE propellant is a new type of propellant with high energy and good low‐temperature mechanical properties. However, due to the lack of detailed research on its microscopic pyrolysis and oxidation mechanism, its combustion performance is challenging to regulate, limiting the further development. Therefore, a core‐shell nanoparticle model (Al/Al2 O3 /HMX/NEPE) with 12257 atoms is constructed in this paper. Based on the above force field, we mainly analyze the behavior of high temperature pyrolysis. At the same time, key intermediate products and key original reactions are obtained. It is found that the pyrolysis and oxidation of NEPE propellant can be roughly divided into three stages: (1) Pyrolytic warming stage (0–200 ps), (2) Rapid reaction stage (200–400 ps), (3) Stable reaction stage (400–1200 ps). The pyrolysis and oxidation of HMX/NEPE on the Al(Aluminium) core surface is essentially a gradual fracture of the macromolecular structure. Due to high temperature pyrolysis, a large amount of NO2, NO, NH and NH2 are produced in the system. NO, NO2 interacts with NH and NH2, resulting in the rapid accumulation of N2 and H2 O while generating a large amount of heat, which is the main reason for the heating of the system. The present study would contribute to the formulation design and combustion performance regulation of NEPE solid propellants, which is an essential reference value. Abstract :